Ms. Perancangan Jaringan IoT Smart Home Untuk Meningkatkan Efisiensi Otomasi dan Keamanan Sistem - Raden Najla Ramadhani; Icha Marisa Mahmuda; Merista Aulia; Nayla Jasmine; Johannes Hamonangan Siregar (Universitas Aisyiyah Surakarta, 2026)
The Internet of Things (IoT) provides innovation in the application of smart home systems to improve comfort, energy efficiency, and home security. However, smart home systems still face major problems in the form of electricity waste and network security due to the large number of IoT devices in a single network, which requires adequate segmentation. This study aims to design a smart home IoT network to improve energy efficiency and network security in smart home systems by applying VLAN segmentation using Cisco Packet Tracer. The system development uses the Network Development Life Cycle (NDLC) model method by implementing the analysis, design, simulation, implementation, monitoring, and management phases. Simulation was performed using Cisco Packet Tracer by integrating 13 IoT devices, including smart lamps, smart doors, smart garages, and webcams, connected to an IoT server as a centralized monitoring system. The test results showed that VLAN segmentation successfully separated IoT device and user traffic with low latency ranging from 18-20ms with a 100% connectivity rate, and the automation and monitoring systems could be accessed in real-time via a smartphone. This study proves that the implementation of VLAN segmentation in smart homes effectively improves IoT network security while maintaining efficient communication between devices with optimal performance.